2019
DOI: 10.1111/rsp3.12148
|View full text |Cite
|
Sign up to set email alerts
|

International tourism entrepreneurs in Swedish peripheries: Compliance and collision with public tourism strategies

Abstract: This paper examines the entrepreneurial strategies and development aspirations of immigrant tourism entrepreneurs in rural Sweden, and how they support or conflict with local and regional public sector tourism strategies.Our conceptual framework contrasts the immigrant entrepreneurs' business and lifestyle priorities with public sector responsibilities and development interests. Findings from three case studies suggest that immigrants both collaborate and compete with public sector stakeholders in different to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Although Mattsson and Cassel (2020) agreed that migrant entrepreneurs bring new knowledge, they showed that immigrant entrepreneurs are less likely to engage in value-creating networks with locals and prefer to network with people from their own regions. Carson and Carson (2018) and Eimermann et al (2019) showed similar results from immigrant RT entrepreneurs in Sweden.…”
Section: Thematic Focisupporting
confidence: 56%
“…Although Mattsson and Cassel (2020) agreed that migrant entrepreneurs bring new knowledge, they showed that immigrant entrepreneurs are less likely to engage in value-creating networks with locals and prefer to network with people from their own regions. Carson and Carson (2018) and Eimermann et al (2019) showed similar results from immigrant RT entrepreneurs in Sweden.…”
Section: Thematic Focisupporting
confidence: 56%
“…By pursuing their own objectives associated with a certain lifestyle, TLEs follow their own agenda, and may differ from or conflict with the communication and image strategy implemented by the destination's official entities (c.f. Eimermann et al, 2019). One particular mechanism with strong impact on tourism growth is the creation of incubation programs (Moyle et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many rural municipalities all over the world, including Russia, have turned to tourism in order to stimulate new regional development (Eimermann et al 2019;Almstedt et al 2014). Any kind of substantive pastime of tourists in a rural area can qualify for rural tourism, including cultural, event-related, agrarian tourism, etc.…”
Section: Trajectory Of the Sustainable Tourism Development In The Altai Mountainsmentioning
confidence: 99%